PENGARUH TINGKAT PEMAHAMAN AKUNTANSI, PERSEPSI BIAYA TERHADAP NIAT UNTUK MENGAMBIL SERTIFIKASI PROFESI CHARTERED ACCOUNTANT (CA) DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI - Elis Istanti; Jawoto Nusantoro; Gustin Padwa Sari (Universitas Muhammadiyah Metro, 2020)
This study aims to examine and analyze the influence of accounting understanding level, cost perceptions ofintentions to take Chartered Accountant (CA) professional certification with motivation as a moderatingvariable. This study uses a quantitative method of associative and verification approaches. The object of thisresearch is the S1 Accounting Study Program students at Muhammadiyah University of Metro. The studypopulation was 406 students. The sampling technique used is purposive sampling, so as to obtain a sample of102 students. Data analysis techniques in this study used descriptive statistics, classic assumption tests,moderated regression analysis, hypothesis testing and coefficient of determination tests. Data were analyzedusing SPSS version 20. The results of this study indicate that: 1) The accounting understanding level did notsignificantly influence the intention to take Chartered Accountant (CA) professional certification, 2) Perceptionof cost had a significant effect on the intention to take Chartered Accountant (CA) profession certification, 3) Motivation was able to moderate the relationship between the level of accounting understanding of intention to take Chartered Accountant (CA) professional certification, 4) Motivation was able to moderate the relationshipof perceived cost to intention to take Chartered Accountant (CA) profession certification.